Teachers’ Teaching Strategies in Implementing Merdeka Curriculum at Elementary School - Arofah, Fidella Nur; Imani, Anugrah; Rohadi, Tedi (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Merdeka Curriculum is a curriculum with diverse intracurricular learning, so that students have enough time to learn concepts and strengthen their abilities. Teachers have the freedom to choose various teaching tools so that learning can be tailored to the learning needs and interests of students. Teachers utilize technology to design more creative and innovative teaching methods. Teachers must have strategies in teaching, such as applying various methods, media and games to develop students’ interest in learning English. Creative and innovative teachers are teachers who are able to create various learning activities that are fun and not boring for students and teachers are able to create new learning activities for students. The subjects of this research were English teachers who taught grades one to six. The research method used by researchers is a qualitative method. The data collection techniques are interviews and questionnaires. The aim of this research is to analyze how the teaching strategies used by English teachers are implemented and to evaluate the reasons why teachers use certain English teaching strategies in implementing the Merdeka Curriculum at SD Kreatif Khairu Ummah ’Aisyiyah Cilegon. Based on the research results, the teachers used the Project-Based Learning (PJBL) teaching strategy, Inquiry strategy, Problem Based Learning strategy, and Group Learning and Discussion strategy. The reason is, because the Project-Based Learning (PJBL) teaching strategy, Inquiry strategy, Problem Based Learning strategy, and Group Learning and Discussion strategy make students more active in participating in the learning process, students can learn together and share knowledge with each other.